Refinement of a workflow for human relevance assessment of adverse outcome pathways and associated new approach methodologies - van den Brand, Annick D.; Meerman, Julia J.; Veltman, Christina H. J.; Luijten, Mirjam (Frontiers in Toxicology, 2025)
In chemical risk assessment the human relevance of adverse health effects observed in experimental animal studies and the underlying toxicological mechanisms, i.e., adverse outcome pathways is often assumed, unless evidence suggests otherwise. Yet, detailed systematic guidance as to how human relevance of perturbed AOPs should be assessed and which data or information should be considered is lacking. Building on previous work we present a refined workflow for human relevance assessment of AOPs and associated new approach methodologies The updated workflow structurally defines the required information for assessing the human relevance of the AOP by means of biological and empirical considerations. Furthermore, the modified workflow better guides assessment of the relevance of NAMs. This is of importance for the use of NAM data in human health risk assessment. In addition, we suggest an approach for weight of evidence assessment by integrating the different lines of evidence. The refined workflow is now accompanied by developed guidance and templates as well as an expanded toolbox, i.e., a list of information sources, to further facilitate application of the workflow. Finally, remaining issues and challenges are discussed. This work is a next step towards to the ultimate goal of a harmonized, structured and transparent approach for human relevance assessment of AOPs and associated NAMs.